Development method of low-permeability oil reservoir oily sludge profile control system

By developing polymer gel-type profile modifiers, the problem of difficult injection of oil-containing sludge in low-permeability reservoirs is solved, and its effective sealing and sludge treatment in the formation is achieved, which improves oil production efficiency and on-site management.

CN119534760APending Publication Date: 2025-02-28YANCHANG OIL FIELD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411576551.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The oil-containing sludge in low-permeability reservoirs is difficult to flow due to its high viscosity, which makes it difficult to inject and cannot be directly used for formation sealing.

Method used

Develop polymer gel-type profile modifiers, and select suitable polymers, crosslinking agents and stabilizers to optimize polymer concentration and crosslinking agent concentration to form a high viscosity gel system, suspend and carry oil-containing sludge to meet pumpability.

Benefits of technology

The pumpability of oil-containing sludge is achieved, so that it can enter the formation smoothly, effectively seal the formation cracks and high-permeability zones, and at the same time solve the problem of a large amount of oil-containing sludge accumulation on the oil production plant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119534760A_ABST
    Figure CN119534760A_ABST
Patent Text Reader

Abstract

The invention provides a low permeability reservoir oily sludge profile control system development method, which comprises: S1, screening a polymer and a cross-linking agent, analyzing the compatibility of the polymer and oily sludge, and analyzing the gelling performance of a polymer solution mixed with the oily sludge; s2, optimizing the concentration of the polymer; s3, optimizing the concentration of a cross-linking agent; s4, optimizing the concentration of a cross-linking auxiliary agent; s5, optimizing the concentration of the stabilizer; and S6, optimizing the concentration of the oily sludge. According to the development method of the low-permeability oil reservoir oily sludge profile control system, oily sludge can be suspended and carried, the pumpability is met, the oily sludge can smoothly enter a stratum, and effective plugging of stratum cracks and high-permeability zones is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for developing a profile control system for oily sludge in a low permeability oil reservoir. Background Art

[0002] Oily sludge contains a certain amount of heavy oil and solid particles, which has a certain plugging effect. However, due to its high viscosity under ground temperature environment, it basically has no fluidity, is difficult to inject, and cannot be used directly. For this reason, it is necessary to develop polymer gel profile control agents, which use the high viscosity of polymer gel to suspend and carry oily sludge to meet pumpability, so that oily sludge can smoothly enter the formation and effectively plug formation cracks and high permeability zones. At the same time, an oily sludge emulsification system is developed to process a large amount of oily sludge and inject it back into the formation, in order to solve the actual problem of large amounts of oily sludge currently accumulated on site in oil production plants. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a method for developing an oily sludge profile control system for low permeability oil reservoirs, which can suspend and carry oily sludge to meet pumpability, so that the oily sludge can smoothly enter the formation and achieve effective blocking of formation cracks and high permeability zones.

[0004] The technical solution of the present invention is: a method for developing a low permeability oil reservoir oil-containing sludge profile control system, which is special in that it includes the following steps:

[0005] S1. Screening of polymers and cross-linkers, including:

[0006] S1.1. Analyze the compatibility of polymers with oily sludge;

[0007] S1.2. Analyze the gelling properties of the polymer solution mixed with oily sludge;

[0008] S2, optimizing the polymer concentration;

[0009] S3, optimizing the concentration of the cross-linking agent;

[0010] S4, optimizing the concentration of the cross-linking aid;

[0011] S5. Optimizing the concentration of the stabilizer;

[0012] S6. Optimize the concentration of oily sludge.

[0013] Furthermore, the analysis of the compatibility of the polymer with the oily sludge in step S1.1 specifically includes: at room temperature, the selected polymer is respectively configured into 1000 mg / L, 2000 mg / L and 3000 mg / L polymer solutions, 20% of the oily sludge is added to each of them, and the viscosity changes thereof are measured at different times to observe the compatibility with the polymer.

[0014] Furthermore, the step S1.2 specifically includes: adding two cross-linking agents, a chromium ion cross-linking agent and an organic phenolic formaldehyde, respectively to the mixed solution of the polymer and the oily sludge in the above step S1.1, and observing the gelling condition.

[0015] Furthermore, the step S2 is to optimize the polymer concentration by:

[0016] Preparation of experimental mother solution and target solution:

[0017] (1) Weigh 1000 g of experimental water in a 1000 mL beaker and place it in a constant temperature water bath at 45 °C;

[0018] (2) Weigh 5.00 g of hydrophobic associating polymer AP-P4;

[0019] (3) Add the weighed sample under stirring and vortexing conditions (the sample must be added to the vortex);

[0020] (4) Stir and dissolve completely and place for 24 hours for later use;

[0021] (5) Weigh a certain amount of the mother solution to be used according to the calculation, then dilute it with experimental water to prepare the target solution, and stir it evenly;

[0022] Use distilled water to prepare the mother solution of crosslinking agent W, crosslinking aids B and JB, stabilizer L, and fungicide JQ to a concentration of 10000 mg / L, and let it stand for 48 hours before use;

[0023] The hydrophobic associating polymer AP-P4 was prepared into target solutions of different concentrations using experimental water. Different concentrations of cross-linking agents and the same concentration of cross-linking aids were added and placed in an oven at 60°C. The strength changes of the colloid were measured at different times to determine the effect of polymer concentration on the gelation time and gelation strength.

[0024] Furthermore, the step S3 is to optimize the concentration of the cross-linking agent as follows:

[0025] The mother solution of hydrophobic associating polymer AP-P4 was diluted with experimental water to prepare target solutions of the same concentration. Different concentrations of cross-linking agents were added and placed in an oven at 60°C. The strength changes of the colloid were measured at different times to determine the gelation time and strength after gelation.

[0026] Furthermore, the step S4 is to optimize the concentration of the cross-linking aid as follows:

[0027] The mother solution of hydrophobic associating polymer AP-P4 was diluted with experimental water to prepare target solutions of the same concentration. The same concentration of cross-linking agent and different concentrations of cross-linking aid were added and placed in an oven at 60°C. The strength changes of the colloid were measured at different times to determine the gelation time and strength after gelation.

[0028] Furthermore, the step S5 optimizes the concentration of the stabilizer by:

[0029] The mother solution of hydrophobic associating polymer AP-P4 was diluted with experimental water to prepare target solutions of the same concentration. The same concentration of cross-linking agent and different concentrations of stabilizer were added and placed in an oven at 60°C. The strength changes of the colloid were measured at different times to determine the gelation time and strength after gelation.

[0030] Furthermore, the step S6 of optimizing the concentration of oily sludge is specifically as follows:

[0031] The oily sludge is directly sampled from the site without being diluted with water, and the amount of the oily sludge added to the gel system is optimized.

[0032] The beneficial effects of the present invention are as follows: through the method for developing a low permeability reservoir oily sludge profile control system proposed by the present invention, a polymer gel profile control agent can be developed, and the high viscosity of the polymer gel is used to suspend and carry the oily sludge, so as to meet the pumpability, so that the oily sludge can smoothly enter the formation, and effectively block the formation fractures and high permeability zones. At the same time, an oily sludge emulsification system is developed, which can process a large amount of oily sludge and inject it back into the formation, so as to solve the actual problem of a large amount of oily sludge being accumulated on site in oil production plants. . BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the change graph of 1000mg / L HPAM mixed with oily sludge over time;

[0034] Figure 2 This is the change graph of 2000mg / L HPAM mixed with oily sludge over time;

[0035] Figure 3 This is the graph showing the changes over time after 3000 mg / L HPAM was mixed with oily sludge;

[0036] Figure 4 The viscosity curve of the mixed solution of HPAM and oily sludge changes with time;

[0037] Figure 5 This is a graph showing the changes over time after 1000 mg / L of hydrophobic associating polymer AP-P4 was mixed with oily sludge;

[0038] Figure 6This is a graph showing the changes over time after 3000 mg / L of hydrophobic associating polymer AP-P4 was mixed with oily sludge;

[0039] Figure 7 This is a graph showing the changes over time after 3000 mg / L of hydrophobic associating polymer AP-P4 was mixed with oily sludge;

[0040] Figure 8 The viscosity curve of the mixed solution of AP-P4 and oily sludge changes with time;

[0041] Fig. 9 The effect of polymer concentration on profile control system under different cross-linking agent concentrations;

[0042] Fig.10 The effect of the cross-linking agent W concentration on the profile control system at different polymer concentrations;

[0043] Fig.11 The effect of the concentration of cross-linking agent B on the profile control system;

[0044] Fig.12 The effect of the concentration of cross-linking agent JB on the profile control system;

[0045] Fig.13 The effect of stability L concentration on the profile control system;

[0046] Fig.14 This is the effect of adding oily sludge on the profile control system. DETAILED DESCRIPTION

[0047] The present invention provides a method for developing a low permeability oil reservoir oily sludge profile control system. The formula screening of the oily sludge profile control agent system mainly includes four aspects: (1) comparing the performance of various polymers, screening out polymers that have good compatibility and suspension with oily sludge, and can form gels to suspend and carry oily sludge. (2) Screening out a cross-linking agent that can cross-link the polymer solution mixed with oily sludge. (3) Screening out a suitable cross-linking auxiliary agent. (4) Screening out a suitable amount of oily sludge.

[0048] The water quality of the experimental water used in this embodiment is shown in Table 1, and the water quality of the injection water in the region is selected as the standard.

[0049] Table 1 Basic composition of experimental water

[0050]

[0051] The components of the Huaziping oily sludge sample obtained in this embodiment are as follows: rust content: 7.1%, mud content: 41.9%, water content: 18.7%, oil content: 33.5%, wherein the water content and oil content are measured by weighing samples separately, so that the sum of the percentages of all substances in the final result is 101.2%, which is within the normal experimental error. The water content of this oily sludge sample is relatively low. Considering the general actual situation on site, the water content of the oily sludge sample is generally around 60% to 80%. In the experiment of this embodiment, in order to better simulate the actual situation on site, the oily sludge sample is first diluted with experimental water to make its water content reach about 80%, and then used for the experiment. In the experiment of this embodiment, the composition of the oily sludge in Table 2 is as follows:

[0052] Table 2 Composition of oily sludge used in the experiment

[0053] Oily sludge Water Oil Clay rust content(%) 79.675 8.375 10.475 1.775

[0054] (1) Polymer and cross-linker screening

[0055] At the Changqing Oilfield Production Plant No. 4, according to the actual situation of the reservoir, the goal is to seal cracks and high-permeability channels, adjust the permeability gradient, improve the water absorption profile, and improve the oil displacement efficiency and swept volume. This requires that the polymer solution of the gel system in the oily sludge profile control agent has good performance: it can form a good colloid and have a certain viscosity so that it can suspend and carry the oily sludge well. At the same time, since there are more impurities and chemicals in the oily sludge, it has a greater impact on the polymer solution, and the polymer solution is required to have good compatibility with the oily sludge.

[0056] 1) Compatibility analysis of polymer and oily sludge

[0057] As the main polymer of the gel system in the oily sludge profile control agent, four commonly used polymers were selected for screening, namely:

[0058] Hydrophobic associating polymer AP-P4, molecular weight 12 million, Sichuan Guangya Technology Co., Ltd.

[0059] Ordinary HPAM, molecular weight about 25 million, Beijing Hengju Company

[0060] Ordinary HPAM, molecular weight about 17 million, Beijing Hengju Company

[0061] MO4000, molecular weight about 25 million, Japan

[0062] At room temperature, 20% oily sludge was directly added to 1000mg / L, 2000mg / L and 3000mg / L polymer solutions, respectively, and the viscosity changes were measured at different times to observe its compatibility with the polymer.

[0063] Experimental results:

[0064] The experimental results show that oily sludge has a great influence on the four polymers. After the oily sludge is directly added, the viscosity of the four polymers at each concentration immediately decreases significantly.

[0065] We selected HPAM with a molecular weight of about 25 million and hydrophobic associating polymer AP-P4 with a molecular weight of 12 million as representative experimental results. The phenomena are as follows:

[0066] HPAM, molecular weight about 25 million;

[0067] The changes of 1000mg / L HPAM and oily sludge over time are as follows Figure 1 As shown;

[0068] The changes of 2000mg / L HPAM and oily sludge over time are as follows Figure 2 As shown;

[0069] The changes of 3000mg / L HPAM and oily sludge over time are as follows Figure 3 shown.

[0070] Table 3 Changes in viscosity of HPAM and oily sludge mixed solution over time

[0071]

[0072] Hydrophobic associating polymer AP-P4, molecular weight 12 million

[0073] The changes of 1000 mg / L hydrophobic associating polymer AP-P4 with oily sludge over time are shown in Figure 2. Figure 5 As shown;

[0074] The changes of 2000mg / L hydrophobic associating polymer AP-P4 with oily sludge over time are shown in Figure 2. Figure 6 As shown;

[0075] The changes of 3000mg / L hydrophobic associating polymer AP-P4 with oily sludge over time are shown in Figure 2. Figure 7 As shown;

[0076] Table 4 Changes of viscosity of mixed solution of AP-P4 and oily sludge over time

[0077]

[0078] From Tables 3, 4 and Figure 4 , 8It can be seen that the viscosity of the polymer solution drops rapidly when the sludge is just mixed, and the viscosity of the sample solution is much lower than the viscosity of the original mother liquor, indicating that the various complex components in the oily sludge have a great influence on the polymer solution. The experimental results show that the higher iron, crude oil, and microorganisms in the oily sludge have a greater impact on the polymer colloid. The solid particle size distribution in the oily sludge has higher requirements for the suspension of the polymer solution. The viscosity of the hydrophobic associating polymer AP-P4 after mixing with the oily sludge for the same time is greater than that of HPAM (molecular weight 25 million), indicating that the hydrophobic associating polymer AP-P4 is better than HPAM (molecular weight 25 million) in resisting the influence of oily sludge.

[0079] 2) Gelation performance of polymer solution mixed with oily sludge

[0080] In order to make the oily sludge profile control agent achieve the purpose of adjusting the permeability difference, improving the water absorption profile, and increasing the oil displacement efficiency and swept volume, it is necessary to require that the polymer mixed with oily sludge can form a good colloid with good performance when a cross-linking agent is added. Therefore, it is necessary to investigate the gelling properties of the polymer solution mixed with oily sludge. Two cross-linking agents, chromium ion cross-linking agent EC and organic phenolic aldehyde, were added to the mixed solution of four polymers and oily sludge to observe the gelling properties.

[0081] The experimental scheme is as follows:

[0082] Table 5 Experimental scheme of gelling performance

[0083]

[0084] Experimental results:

[0085] Table 6 Experimental results of chromium ion crosslinker EC gelling performance

[0086]

[0087] It can be seen from Table 6 that in the case of chromium ion crosslinker EC, the four polymers basically do not gel and the viscosity decreases significantly. This may be because the high content of rust, crude oil, bacterial microorganisms and other impurities in the oily sludge has a greater impact on the organic metal crosslinker, causing the polymer solution to not gel.

[0088] Table 7 Experimental results of gelling performance of organic phenolic crosslinking agent

[0089]

[0090]

[0091] It can be seen from Table 7 that in the case of organic phenolic crosslinking agent, the four polymers are able to form gels, among which the hydrophobic associating polymer AP-P4 exhibits better gelling properties and resistance to the influence of oily sludge.

[0092] After comprehensive consideration of the above two aspects, this example decided to use the hydrophobic associating polymer AP-P4 as the main polymer agent of the oily sludge profile control agent, and the organic phenol formaldehyde as the main cross-linking agent.

[0093] (2) Optimal polymer concentration

[0094] In the deep profile control operation of polymer gel, the amount of polymer is the key parameter that directly affects the gelling strength and technical and economic indicators, so in the oily sludge gel profile control agent, the amount of polymer is the key parameter. Therefore, it is very important to study the influence of polymer concentration in the oily sludge gel profile control agent on the gelling performance of the oily sludge profile control system under the conditions of reservoir temperature and injection water.

[0095] Preparation of experimental mother solution and target solution:

[0096] (1) Weigh 1000 g of experimental water in a 1000 mL beaker and place it in a constant temperature water bath at 45 °C;

[0097] (2) Weigh 5.00 g of hydrophobic associating polymer AP-P4;

[0098] (3) Add the weighed sample under stirring and vortexing conditions (the sample must be added to the vortex);

[0099] (4) Stir and dissolve completely and place for 24 hours for later use;

[0100] (5) Weigh a certain amount of the mother solution to be used according to the calculation, then dilute it with experimental water to prepare the target solution, and stir it evenly;

[0101] Use distilled water to prepare the mother solution of crosslinking agent W, crosslinking aids B and JB, stabilizer L, and fungicide JQ to a concentration of 10000 mg / L, and let it stand for 48 hours before use;

[0102] The hydrophobic associating polymer AP-P4 was prepared into target solutions of different concentrations using experimental water. Different concentrations of cross-linking agents and the same concentration of cross-linking aids were added and placed in an oven at 60°C. The strength changes of the colloid were measured at different times to determine the effect of polymer concentration on the gelation time and gelation strength.

[0103] According to the experimental results (Table 8 and Fig. 9 ) It can be seen that the polymer concentration has a certain influence on the gel strength, and the system viscosity increases with the increase of polymer concentration.

[0104] Experimental results:

[0105] Table 8 Effect of polymer concentration on profile control system at different crosslinking agent concentrations (a) Effect of polymer concentration on profile control system when W is 300 mg / L

[0106]

[0107] (b) Effect of polymer concentration on profile control system when W is 500 mg / L

[0108]

[0109] From Table 8 and Fig. 9 It can be seen that when the concentration of the hydrophobic associating polymer is 1000 mg / L, the system can also gel, but the viscosity is relatively low, 1480-2740 mPa.s, and the critical concentration can be determined as 1000 mg / L; when the concentration of the hydrophobic associating polymer is 2000 mg / L, the viscosity of the gel system can reach 6980-9050 mPa.s. When the concentration of the hydrophobic associating polymer is 3000 mg / L, the viscosity of the gel system can reach 10400-15900 mPa.s.

[0110] The addition of oily sludge will cause the gelling strength of AP-P4 to decrease, but the large amount of oily sludge solid particles it carries can effectively seal cracks and high permeability layers.

[0111] (3) Optimal crosslinking agent concentration

[0112] The crosslinking agent in the oily sludge gel profile control system is a key factor affecting the comprehensive effect. Therefore, it is necessary to conduct in-depth research on the influence of the crosslinking agent concentration on the system's gelling properties in order to obtain a formula system that meets the requirements of on-site construction technology and is flexible in regulation.

[0113] The mother solution of hydrophobic associating polymer AP-P4 was diluted with experimental water to prepare target solutions of the same concentration. Different concentrations of cross-linking agents were added and placed in an oven at 60°C. The strength changes of the colloid were measured at different times to determine the gelation time and strength after gelation.

[0114] Experimental results:

[0115] Table 9 Effect of crosslinker W concentration on profile control system when polymer concentration is 2000 mg / L

[0116]

[0117] Table 10 Effect of crosslinker W concentration on profile control system when polymer concentration is 3000 mg / L

[0118]

[0119] From Tables 9, 10 and Fig.10 It can be seen that the greater the cross-linking agent concentration, the faster the gel system of the oily sludge profile control agent gels and the greater the colloid strength. However, when the cross-linking agent concentration is high, the stronger the colloid strength, the more likely the gel system is to be over-cross-linked, resulting in poor stability and colloid dehydration. At the same time, it can be obtained that when the concentration of the hydrophobic associating polymer AP-P4 is 2000 mg / L, the appropriate amount of cross-linking agent W is 400-700 mg / L; when the concentration of AP-P4 is 3000 mg / L, the appropriate amount of cross-linking agent W is 600-700 mg / L.

[0120] (4) Optimal concentration of cross-linking aid

[0121] The cross-linking agent in the oily sludge gel profile control system is also a key factor affecting the overall effect. It is necessary to conduct in-depth research on the influence of the concentration of the cross-linking agent on the gelling properties of the system in order to obtain a flexible formula system that meets the requirements of the on-site construction process.

[0122] The mother solution of hydrophobic associating polymer AP-P4 was diluted with experimental water to prepare target solutions of the same concentration. The same concentration of cross-linking agent and different concentrations of cross-linking aid were added and placed in an oven at 60°C. The strength changes of the colloid were measured at different times to determine the gelation time and strength after gelation.

[0123] Experimental results:

[0124] (1) Cross-linking agent B

[0125] Table 11 Effect of cross-linking agent B concentration on profile control system

[0126]

[0127] From Table 11 and Fig.11 It can be seen that crosslinking aid B has a certain effect on the gel strength. As the concentration of B increases, the gel strength rises rapidly; when the concentration reaches 500 mg / L, the increase in gel strength becomes slow. When the concentration of crosslinking aid B reaches 500 mg / L, the strength of the system after gelation is 16530 mPa.s. Crosslinking aid B also has a great effect on the stability of the system after gelation. The system without B begins to dehydrate after 20 days, while the system with 500 mg / L crosslinking aid B does not dehydrate within 3 months. Adding an appropriate amount helps stabilize the colloid. Therefore, we choose a crosslinking aid B concentration of 500 mg / L.

[0128] (2) Cross-linking agent JB

[0129] Table 12 Effect of cross-linking agent JB concentration on profile control system

[0130]

[0131] From Table 12 and Fig.12 It can be seen that the crosslinking agent JB has little effect on the strength after gelation, but during the gelation process, it has a great influence on the gelation time of the system, has a good coagulation effect, and can adjust the gelation time. In addition, the crosslinking agent JB has a great influence on the stability of the system. The system without JB began to dehydrate after 15 days. Therefore, we selected the crosslinking agent JB concentration of 200 mg / L.

[0132] (5) Optimal Stabilizer Concentration

[0133] The stabilizer in the oily sludge gel profile control system is also a key factor affecting the overall effect. It is necessary to conduct in-depth research on the influence of stabilizer concentration on the gelling properties of the profile control system in order to obtain a flexible formula system that meets the requirements of on-site construction technology.

[0134] The mother solution of hydrophobic associating polymer AP-P4 was diluted with experimental water to prepare target solutions of the same concentration. The same concentration of cross-linking agent and different concentrations of stabilizer were added and placed in an oven at 60°C. The strength changes of the colloid were measured at different times to determine the gelation time and strength after gelation.

[0135] Experimental results:

[0136] Table 13 Effect of stability L concentration on profile control system

[0137]

[0138]

[0139] From Table 13 and Fig.13 It can be seen that stabilizer L has little effect on the strength of the gel when the concentration is below 200 mg / L, but when the concentration is greater than 200 mg / L, its viscosity drops significantly and the gel is weak. When the concentration is below 100 mg / L, its colloid stability is not very ideal and the colloid dehydration time is fast. Therefore, we choose L concentration of 150-200 mg / L.

[0140] (6) Optimization of oily sludge concentration

[0141] Oily sludge profile control agent mainly suspends and carries oily sludge solid particles, and uses gel and solid particles to work together to achieve effective plugging of formation fractures and high permeability zones. The amount of oily sludge added plays a vital role in the entire profile control agent. At the same time, the amount of oily sludge added will also affect the performance of the gel system. Therefore, the amount of oily sludge added to the gel system must be optimized.

[0142] In this experiment, in order to fully consider the effect of oily sludge addition on the profile control system, oily sludge directly sampled from the site without dilution with water was used, with a water content of 18.7%.

[0143] Table 14 Effect of oily sludge addition on profile control system

[0144]

[0145] From Table 14 and Fig.14 It can be seen that the amount of oily sludge added has a greater impact on the colloid. When the amount of oily sludge added is more, the colloid strength is weaker. This shows that the various complex components in the oily sludge have a greater impact on the colloid. When more sludge is added, more complex components are added, so the impact on the colloid will be greater. The experimental results show that when adding oily sludge with a moisture content of 18.7%, it is better to control the amount below 5%.

Claims

1. A method for developing a profile control system for oily sludge in low permeability reservoirs, characterized in that: The following steps are involved: S1. Screening of polymers and cross-linkers, including: S1.

1. Analyze the compatibility of polymers with oily sludge; S1.

2. Analyze the gelling properties of the polymer solution mixed with oily sludge; S2, optimizing the polymer concentration; S3, optimizing the concentration of the cross-linking agent; S4, optimizing the concentration of the cross-linking aid; S5. Optimizing the concentration of the stabilizer; S6. Optimize the concentration of oily sludge.

2. The method for developing a profile control system for oily sludge in low permeability reservoirs according to claim 1, characterized in that: The analysis of the compatibility of the polymer with the oily sludge in step S1.1 specifically includes: at room temperature, the selected polymer is respectively configured into 1000 mg / L, 2000 mg / L and 3000 mg / L polymer solutions, 20% of the oily sludge is added to each of them, and the viscosity changes thereof are measured at different times to observe the compatibility with the polymer.

3. The method for developing a profile control system for oily sludge in low permeability reservoirs according to claim 2, characterized in that: The step S1.2 specifically includes: adding two cross-linking agents, a chromium ion cross-linking agent and an organic phenolic formaldehyde, respectively to the mixed solution of the polymer and the oily sludge in the above step S1.1, and observing the gelling condition.

4. The method for developing a profile control system for oily sludge in low permeability reservoirs according to claim 3, characterized in that: The step S2 of optimizing the polymer concentration is specifically as follows: Preparation of experimental mother solution and target solution: (1) Weigh 1000 g of experimental water in a 1000 mL beaker and place it in a constant temperature water bath at 45 °C; (2) Weigh 5.00 g of hydrophobic associating polymer AP-P4; (3) Add the weighed sample under stirring and vortexing conditions (the sample must be added to the vortex); (4) Stir and dissolve completely and place for 24 hours for later use; (5) Weigh a certain amount of the mother solution to be used according to the calculation, then dilute it with experimental water to prepare the target solution, and stir it evenly; Use distilled water to prepare the mother solution of crosslinking agent W, crosslinking aids B and JB, stabilizer L, and fungicide JQ to a concentration of 10000 mg / L, and let it stand for 48 hours before use; The hydrophobic associating polymer AP-P4 was prepared into target solutions of different concentrations using experimental water. Different concentrations of cross-linking agents and the same concentration of cross-linking aids were added and placed in an oven at 60°C. The strength changes of the colloid were measured at different times to determine the effect of polymer concentration on the gelation time and gelation strength.

5. The method for developing a profile control system for oily sludge in low permeability reservoirs according to claim 4, characterized in that: The step S3 of optimizing the concentration of the cross-linking agent is specifically as follows: The mother solution of hydrophobic associating polymer AP-P4 was diluted with experimental water to prepare target solutions of the same concentration. Different concentrations of cross-linking agents were added and placed in an oven at 60°C. The strength changes of the colloid were measured at different times to determine the gelation time and strength after gelation.

6. The method for developing a profile control system for oily sludge in low permeability reservoirs according to claim 5, characterized in that: The step S4 is to optimize the concentration of the cross-linking aid as follows: The mother solution of hydrophobic associating polymer AP-P4 was diluted with experimental water to prepare target solutions of the same concentration. The same concentration of cross-linking agent and different concentrations of cross-linking aid were added and placed in an oven at 60°C. The strength changes of the colloid were measured at different times to determine the gelation time and strength after gelation.

7. The method for developing a profile control system for oily sludge in low permeability reservoirs according to claim 6, characterized in that: The step S5 of optimizing the concentration of the stabilizer is specifically as follows: The mother solution of hydrophobic associating polymer AP-P4 was diluted with experimental water to prepare target solutions of the same concentration. The same concentration of cross-linking agent and different concentrations of stabilizer were added and placed in an oven at 60°C. The strength changes of the colloid were measured at different times to determine the gelation time and strength after gelation.

8. The method for developing a profile control system for oily sludge in low permeability reservoirs according to claim 7, characterized in that: The step S6 of optimizing the concentration of oily sludge is specifically as follows: The oily sludge is directly sampled from the site without being diluted with water, and the amount of the oily sludge added to the gel system is optimized.